Les mesures de santé et sécurité au travail auprès des travailleurs étrangers temporaires dans les entreprises saisonnières - Sylvie Gravel; Francisco Villanueva; Stéphanie Bernstein; Jill Hanley; Daniel Crespo; Emmanuelle Ostiguy (Perspectives Interdisciplinaires sur le Travail et la Santé)
An analysis of practical occupational health and safety at work (OHS) was conducted as part of a study on the management issues and working and living conditions of temporary foreign workers (TFW ) employed in horticulture, food processing, and other non-agricultural sectors. This qualitative analysis was based on two data files. Individual interviews were conducted with key stakeholders : employers (n = 17), representatives from non-governmental organizations (n = 13), representatives from a workers’ protection commission (n = 3), and government officials (n = 7). Four focus groups were conducted with the TFWs (n = 31). According to the key stakeholders, the frequency of occupational injuries among TFWs is not particularly worrying, although government OHS watchdogs are not able to document the situation of TFWs. The results of the analysis indicate that preventive OHS practices are uneven, ranging from worst (Spanish summary of instructions included in the employee handbook) to best practices (videos, simulations, tailored training in Spanish, pictograms), including companionship with a Spanish-speaking or bilingual foreman. According to consular and union representatives, two OHS issues deserve special attention : handling of pesticides and road accidents. Several OHS practices among TFWs should be improved, including training for safe handling of pesticides, which is a practice that should be imposed on all businesses, large and small. Adaptation measures for OHS protection are a moral obligation to the TFWs, who are part of the Quebec economy.